Treinamento físico e hiperóxia em dislipidêmicos com idade de 50 a 70 anos - Martins, Amanda Simões (2021)
The highest mortality rates in the world are linked to non-communicable chronic diseases, with a cardiovascular disease presenting the highest prevalence. Dyslipidemia is among the risk factors and causes of the disease. Aging and a sedentary lifestyle tend to aggravate this condition. Measures that can increase lipid metabolism and reduce dyslipidemia rates are desirable in prevention through lifestyle changes. The greatest mobilization of lipids occurs in situations of greater availability of oxygen or greater energy consumption with exercise. This study aims to evaluate the effect of physical training and chronic intermittent hyperoxia on performance, blood lipids and ergospirometric variables of dyslipidemic patients aged 50 to 70 years. Method: 14 people (10 women and 4 men) with a mean age of 59.9 ± 5.04 years, with dyslipidemia were selected. They were collected at pre- and post-test composed of: ergospirometric assessment in normoxia, anthropometric assessment, metabolic assessment, with 20 training sessions being performed between tests. Training took place at a frequency of 3x/week consisting of 2 sets of 10 minutes of walking/running and 5 minutes of gymnastic exercises using body weight. The series were interspersed with 15 minutes of hyperoxia. Data analysis for comparison between pre and post-experimental test using non-parametric statistics, the Wilcoxon test. The results results decrease decreases (p < 0.05) in body mass (- 1.65%) and BMI (pre-test: 29.78 ± 3.60 post-test: 29.29 ± 3.55). Important decreases (p <0.05) were found in the Estimated Mean Glucose (pre-test: 150 ± 81.3 post-test: 121.3 ± 21.3) and glycated hemoglobin - HbA1c (pre-test: 6, 85 ± 2.8 post-test: 6.0 ± 0.86). Modification of Total Cholesterol (pre-test: 251 ± 36.8 post-test: 222.6 ± 31.4) and triglycerides (pre-test: 338.4 ± 401.8 post-test: 201.4 ± 131.0) were important (p <0.05), with no change (p> 0.05) in high and low density lipoproteins (HDL-c and LDL-c) being observed. Change in ergospirometric variables, VO2 (pre-test: 18.0 ± 6.3 post-test: 16.5 ± 7.0), PETO2 (pre-test: 14.3 ± 0.65 post-test : 14.8 ± 0.68), PETCO2 (pre-test: 5.3 ± 0.47 post-test: 4.9 ± 0.4) were relevant (p < 0.05). Running speed, heart rate, conditions and respiratory exchange ratio were statistically equal (p>0.05) in pre- and post-test comparison. The calculated effects (p <0.05) found in the anthropometric and metabolic variables evaluated were a consequence of the combination of physical training and hyperoxia, but, between these two situations, it is not possible to distinguish the effects.